Punching in two-way RC flat slabs with openings and L section columns. Issue 7 (5th August 2019) - Pinto, Valdemir Colares; Branco, Vitor; Oliveira, Denio Ramam
Abstract : Purpose: This study aims to contribute to a better understanding of the influence of the position of openings around L cross-section columns in reinforced concrete flat slabs through a nonlinear computational analysis compared to experimental results. Design/methodology/approach: Tests on four reinforced concrete flat slabs of 1800 x 1800 x 120 mm 3 were carried out under symmetrical punching; one slab was referenced (without hole) and three had square holes of 100 x 100 mm 2 close to columns and with centroid on the critical perimeter at 0.5 d and 2.0 d of the loaded area. A nonlinear analysis of the slabs was performed to aid the interpretation and preview of the experimental results, and to estimate the ultimate loads and failure modes. These estimates followed recommendations of ACI 318, Eurocode 2, NBR 6118, MC 2010 and critical shear crack theory. Findings: The results showed that the presence of holes in the analyzed regions does not influence significantly the behavior of the slabs, leading to conservative structural design once the ultimate load estimates are low, while the computational results adequately estimated the slabs' behavior. Research limitations/implications: A few limitations were observed on how to implement the correct modeling system for computational nonlinear simulation. Practical implications: All design codes underestimated failure loads and the theoretical method was not much better. The nonlinear computational simulations were satisfactory, presenting results close to experimental ones (97 per cent accuracy). Computational simulation also showed that the presence of holes does not significantly influence the load-vertical displacement behavior or failure loads. Social implications: Structural and civil engineers and designers can observe with better details the punching phenomenon and make take secure decisions to building projects. They can preview accurate cases that are not cited in design codes and literature. Originality/value: This is a very rare subject in literature that interests the entire scientific community and especially reinforced concrete designers. Presenting a new methodology to nonlinear flat slab with openings modeling to punching shear provoked by L cross section columns, case that is not cited in literature and design codes.